Analysis and critique how to engage and write about anything - Armstrong, Dorsey 1970- (Chantilly, Virginia The Great Courses, 2011)
All writing--whether it's an essay, a personal letter, or a detailed business report--is at its most memorable when it's built on the fundamental and critical skills that transform your words from good to great. The first lectures provide the first key to more engaging and effective writing: understanding literary genres and the ways their unique styles can shape and inform your own voice. The focus then shifts to the art of rhetoric and the ways it can help you adapt your writing to a variety of situations. The final part is a step-by-step guide through the writing process in its four major stages: researching, first draft, editing and rewriting.
How to write about anything ; How to be an effective reader ; How literature can help ; Shaping your voice ; Knowing your reader ; Art of the essay : how to start How to organize an argument ; Supporting your argument ; Finishing strong ; Uses of poetry ; Poetic diction and syntax ; Drama : writing out loud ; ; What you can learn from autobiography ; Writing and leadership ; Rules of rhetoric ; Invention and arrangement ; Ethos and pathos ; Finding what you need ; Using what you find ; Getting started : writing first drafts ; Editing : finding what's wrong ; Rewriting : fixing what's wrong ; Avoiding common errors in grammar and usage ; The power of words.
Includes bibliographical references.
Keywords: Criticism; English language -- Rhetoric; English language -- Writing; Report writing; Authorship